Evaluación in vitro de la eficiacia de tres soluciones de irrigación en la eliminación de hidróxido de calcio mezclado con gel de clorhexidina al 2% y detección de la formación de precipitado de color naranja-marrón después de la remoción; periodo marzo-julio del 2015. - Dias Curay, Marco Fabricio (2015)
The objectives of the following study were to evaluate the effect of various irrigation solutions in removing calcium hydroxide gel mixed with 2% chlorhexidine as intracanal medication; placed in the root canal 40 mandibular premolars and determining the formation of orange-brown precipitate after irrigation with three solutions; Sodium Hypochlorite 1% and 2.5%, Citric Acid 10% and EDTA with 17%.The root canals of 40 premolars have been preparing, using manual instruments “ProTaper” rotation system (Dentsply Maillefer) to F3 file.The medicine gel chlorhexidine 2% and calcium hydroxide was mixed in a portion one by one and placed navi tip and digital tipped. The roots were randomly divided into 4 experimental groups, specifying the irrigation solution used:Group 1 = 1% NaOCl 17% EDTA and 2% chlorhexidine, Group 2 = 2.5% NaOCl, Group 3 = 17% EDTA, Group 4 = 10% citric acid The remaining amount of medicine was evaluated under a stereoscopic microscope using a scoring system 4 degrees Van Der Sluis, determining that group 1 1% NaOCl and 17% EDTA 2% chlorhexidine .it was the most effective in removing medication with a 46% effective; After irrigation, the specimens were also evaluated by the presence/absence of orange-brown only found in the group of 2.5% NaOCl precipitate samples were statistically evaluated by Kruskal-Wallis test. Keywords Irrigating solutions, intracanal medication, chlorhexidine gel 2%, orange-brown precipitate.